Postoperative Chemotherapy Benefits Patients Who Received Preoperative Therapy and Pancreatectomy for Pancreatic Adenocarcinoma. Issue 6 (June 2020) - Perri, Giampaolo; Prakash, Laura; Qiao, Wei; Varadhachary, Gauri R.; Wolff, Robert; Fogelman, David; Overman, Michael; Pant, Shubham; Javle, Milind; Koay, Eugene J.; Herman, Joseph; Kim, Michael; et al.
Abstract : Objective: We sought to determine whether postoperative chemotherapy after preoperative therapy and pancreatectomy for pancreatic ductal adenocarcinoma (PDAC) prolongs survival. Background: Data to support administering postoperative chemotherapy to patients who received preoperative therapy are lacking. Methods: All patients with PDAC who underwent pancreatectomy after preoperative therapy between 2010 and July 2017 at The University of Texas MD Anderson Cancer Center were identified. To control for selection bias, patients who received postoperative therapy and patients who did not were matched by propensity scores based on factors associated with the use of postoperative chemotherapy. Results: Among 245 patients treated with a median of 4 cycles of preoperative treatment and pancreatectomy, 155 (63%) initiated postoperative chemotherapy and 90 (37%) did not. Patients who received postoperative therapy had a higher median cancer antigen 19-9 level before surgery, larger median tumor diameter, higher rate of extrapancreatic invasion, and lower rate of pathologic major response. The propensity-matched cohort comprised 122 patients: 61 who received postoperative chemotherapy and 61 who did not. The median overall survival (OS) and recurrence free survival (RFS) for patients who received postoperative therapy were 42 and 17 months, respectively, versus 32 and 12 months for patients who did not (OS: P = 0.06; RFS: P = 0.04). Postoperative therapy was marginally associated with a longer OS (hazard ratio 0.55, 95% confidence interval 0.29–1.01; P = 0.05) and significantly associated with a longer RFS (hazard ratio 0.55, 95% confidence interval 0.29–0.96; P = 0.04). Conclusions: Despite being administered more frequently to patients with poor prognostic factors, postoperative chemotherapy after preoperative therapy and pancreatectomy for PDAC was of clinical benefit. Abstract : Supplemental Digital Content is available in the text